Management of school education in India - Sood, Neelam; National Institute of Educational Planning and Administration (India) (New Delhi : A.P.H. Pub. Corp., 2003)
Contributed articles.
Decentralisation of school education -- Teachers and teacher management issues -- Supervision and support system -- Education of minorities and disadvantaged groups -- Role of NGOs in school education -- Education and technology -- Financing of of school education.
"National Institute of Educational Planning and Administration".
Includes bibliographical references and index.
BIED
Complimentary copy from BIED
Keywords: School management and organization -- India; Schools decentralization -- India